Semiotic landscapes and discourses of protest in Barcelona: Tourism Kills - Cantero-Exojo, Monica (Moderna Språk, 2020)
This paper considers how the homogeneity of the capitalist narrative of “tourism is good for the economy,” that has been sponsored and perpetuated by the official governmental institutions since the 1960’s Francoism’s desarrollismo period to present day, did not transfer its economic blessings to all social actors. On the contrary, it has generated social conflict, a border of self-interest between the institutional agencies and the local, which has elided possibilities of home-grown prosperity for the locals. The narrative of a homogeneous economic bonanza has created a fantasy that has irrevocably affected the city’s authenticity as an urban space. It has also codified its struggle under pintadas callejeras (written graffiti): “Tourism Kills” written all over the city. This declaration of confrontation presents the citizens of Barcelona with a simple metaphor that represents global mass-tourism as the equivalent of the beginning of the end for the local way of life.